Revision of the subfamily Bactrodinae (Heteroptera, Reduviidae), with a phylogenetic analysis of Bactrodes - Coscarón, Maria Del Carmen; Melo, Maria Cecilia (Zootaxa, 2003)
The subfamily Bactrodinae is revised. Its sole genus includes five species: Bactrodes femoratus (Fabricius), B. biannulatus Stål, B. spinulosus Stål, B. multiannulatus Berg, and B. misionensis, new species. A cladistic analysis; descriptions of the subfamily, the genus, and its species; and a key are included, as well as a map with geographical distributions.